Conceptualizing an individual full-trip tradable credit scheme for multi-modal demand and supply management: The MobilityCoin System - Servatius, Philipp; Hamm, Lisa; Loder, Allister; Bogenberger, Klaus (Frontiers in Future Transportation, 2022)
Economic instruments are considered promising to achieve the urgently needed reduction of greenhouse gas emissions in the transportation sector. In this context, tradable credit schemes have received more and more attention in recent years. These cap-and-trade systems have the primary goal of limiting congestion, but they can also incorporate emission reduction goals. In this paper, we present the conceptual extension of a tradable credit scheme from a congestion and emission-oriented to a holistic, full-trip, multi-modal mobility traffic management system. In addition to the demand it also includes the management of the supply side. The integration of all existing modes into one holistic scheme ensures that the overall system goals are reached as all behavioral responses remain within the system boundaries. The system comprises two key innovations. First, a central agency has the possibility to provide full-trip incentives across modes to support the overall system's goal. Second, users of the system can spend parts of their allocated mobility budget for transport infrastructure upgrades as an addition to paying for mobility or monetizing it on the market. Those innovations are a distinct extension to the idea of tradable credits. Commonly used smartphones would serve as the enabling technology of the proposed system. They offer all technical requirements and almost every citizen has access to one. Smartphones are affordable compared to dedicated traffic management infrastructure and they are flexible to accommodate system changes, e.g., new modes, through software updates. Besides the potential technical implementation, overall design questions, social aspects as well as general implications of the concept are covered.